Online Home Pharmacy Care Prototype - Putri Diana Savita; Dwiky Miftahuda; Winda Alawiyah Safi'a; Prasojo Pribadi; Setiyo Budi Santoso (Prosiding University Research Colloquium, 2022)
This article presents the design of an online pharmacy service application at home. Development of application workflows using software in the draw.io network. The development includes a consultation menu, ordering medication/prescription redemption, camera features to take pictures (prescriptions), payments, and delivery messages.